Spatial distribution of dust deposition within a small drainage basin: Implications for loess deposits in the Negev Desert. Issue 7 (28th May 2014) - Kidron, Giora J.; Zohar, Motti; Starinsky, Abraham; Lancaster, Nick
Abstract Loessial colluvial sediments and aeolian aprons are common deposits in the Negev Desert Highlands. In an attempt to monitor the amounts and distributional pattern of loess, monthly dust measurements were carried out during 2004 to 2006 in 10 cm diameter traps located at 18 stations along four slopes, north‐facing, south‐facing, east‐facing and west‐facing in a second‐order drainage basin near Sede Boqer, Negev Desert Highlands, Israel. Annual total dust depositions ranged between 110 g and 178 g m−2 with an average of 151·1 g m−2. The average annual dust deposition in the catchment was 23·5% higher than the average amount recorded at the hilltops (122·4 g m−2) and may be a consequence of sheltering opportunities in the hilly topography. When analysed according to season and aspect, significantly higher monthly amounts were received during the wet rainy season of December to March (17·0 g m−2), in comparison with the rest of the year (8·1 g m−2). As for the aspect, while no significant differences characterized north‐facing and south‐facing slopes, east‐facing slopes received significantly higher amounts (by 43·3%) than west‐facing slopes, pointing to preferential dust deposition at the leeward slope. Concurring with the classical model that anticipates higher dust deposition at the leeside slope, but in disagreement with some reports published in the literature, the findings of this study were also supported by a field survey that showed preferential loess accumulation at the eastern and north‐eastern aspects. These findings may shed light on distributional patterns of colluvial sediments and aeolian aprons in the Negev, on soil‐forming processes and on past cycles of dust deposition.